Prevalence of Leishmania species among patients with cutaneous leishmaniasis in Qassim province of Saudi Arabia - Rasheed, Zafar (BMC Public Health, 2019)
BACKGROUND: Leishmaniasis is a parasitic infection endemic in more than ninety countries of the world. The cutaneous leishmaniasis (CL) is a most common form of leishmaniasis and it remains to be a major public health issue in Saudi Arabia. This study was undertaken to investigate the Leishmania species responsible for CL infection in different provinces of Qassim, Saudi Arabia. METHODS: Skin biopsies were obtained from CL patients and DNA was extracted using the Magna pure system. Leishmania species were identified by highly specific/sensitive quantitative and qualitative PCR. RESULTS: Out of total 206 CL biopsies, 49.5% biopsies were found to be positive for Leishmania major (L. major), 28.6% biopsies were positive for Leishmania tropica (L. tropica), 3.9% were found to be positive for Leishmania infantum/donovani (L. infantum/donovani). Not only have these, all tested CL biopsies showed negative test for Leishmania mexicana (L. mexicana) and Leishmania viannia (L. viannia). CONCLUSIONS: This is the first comprehensive study that shows the majority of CL in Qassim was caused by L. major and L. tropica. To the best of our knowledge, this is the very first report that shows the occurrence of L. infantum/donovani in Saudi Arabia. This requires higher alert to the Ministry of Health of Saudi Arabia to take proactive actions in preventing the onset of L. major, L. tropica, L. infantum and L. donovani infections.